New modified mesoporous silica nanoparticles with bimetallic Ni-Zr for electroanalytical detection of dopamine - Mohamed Roduan, Mohamad Rafizie Aiman; Saidin, Mohamad Idris; Sidik, Siti Munirah; Abdullah, Jaafar; Md Isa, Illyas; Hashim, Norhayati; Ahmad, Mohamad Syahrizal; Mohd Yazid, Siti Nur Akmar; Ul-Hamid, Anwar; Bahari, Aireen Aina (International Association of Physical Chemists, 2022)
In this research, bimetallic nickel-zirconia supported on mesoporous nanoparticles (Ni-Zr/MSN) were successfully synthesized by a simple in situ electrolysis method. Ni-Zr/MSN were well-characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET) analyzer, field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). Ni-Zr/MSN were then cast onto a modified glassy carbon electrode (Ni-Zr/MSN/GCE) as dopamine (DA) sensor. Under optimal conditions, the sensor showed a linear concentration relationship in the range of 0.3 µM–0.1 mM with a limit of detection of 0.13 µM. The relative standard deviation for 0.1 mM DA solution was 2.1 % (n = 5). The presence of excess catechol, saccharose, glycine, lactose, uric acid, and Cr3+, Fe2+ and Na+ as interferents was negligible, except for uric acid in 10-fold excess. The analytical recovery of the sensor was successfully demonstrated by the determination of DA in DA-containing medicine and wastewater samples. The results presented herein provide new perspectives on Ni-Zr/MSN as a potential nanomaterial in the development of DA sensors.